Técnica de pictogramas para disminuir las dislalias funcionales en los estudiantes del primer año de educación general básica de la Unidad Educativa padre Julián Lorente en el año lectivo 2019 – 2020 - Gordillo Herrera, Tatiana Yadira (2020)
Functional dyslalia is a phonological disorder commonly presented in the preschool stage, that hinders oral communication; that is why the present research has as general objective to reduce functional dyslalia through the pictogram technique in first year of basic general education children, the following methods were used: scientific, analytical-synthetic, statistical-descriptive and hypothetical-deductive; the techniques and instruments were: the test of articulation to repetition (TAR) that was applied to twenty-two children of first year and the survey applied to the teacher, being this the population investigated. When applying the pretest, the existence of functional dyslalia was verified since 100% of the children had difficulty pronouncing some phoneme; with the purpose of minimizing these linguistic problems, the alternative proposal based on pictograms called "OBSERVING AND TALKING LEARNING" was applied, which contributed significantly, since at the time of applying the pretest, a 72.72% decrease of this type of dyslalia was evidenced; thus obtaining improvements in the oral communication in the school environment; self-esteem and social coexistence. That is why it is recommended that school plans include workshops and activities that contain pictograms, are an easily accessible resource, striking, simple, facilitate communication and are used worldwide, in addition to being a visual technique have greater impact on infants.